1983
DOI: 10.1007/bf02540898
|View full text |Cite
|
Sign up to set email alerts
|

Varietal variations in content, characteristics and composition of mango seeds and fat

Abstract: Wide variations were found in the content, characteristics and composition of seed and fat of 43 varieties of mango (Mangifera indica) fruit. The seed in fruit amounted to 3-25% and kernel in seed 54-85% on an as-is basis. The contents of fat, protein and ash in kernel ranged 3.7-12.6, 4.0.8.1 and 1.O-3.7 (% on dry basis), respectively. Acid value of fat varied from 2.1 to 8.8 and unsaponifiahles from 1.0 to 5.3%. The ranges for fatty acids, as determined by gas chromatography, were: 16:0, 3-18; 17:0, traces-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
44
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 2 publications
18
44
4
Order By: Relevance
“…The amounts of major fatty acids of MSK fat determined in this study were in close agreement with that reported by Ali et al (1985) and Abdalla et al (2007), but the amounts varied to a small extent from those reported by Muchiri et al (2012). Moreover, the concentrations of C 18:3 and C 20 in MSK fats were also good in line with that reported by Ali et al (1985) and Lakshminarayana et al (1983) for different mango varieties. However, the investigated fatty acid profiles of the promising MSK fats were also good in line with that reported by many researchers in the literature (Abdalla et al, 2007;Ali et al, 1985;Lakshminarayana et al, 1983;Solís-Fuentes & Durán-de-Bazúa, 2004).…”
Section: Fatty Acid Compositionssupporting
confidence: 90%
See 3 more Smart Citations
“…The amounts of major fatty acids of MSK fat determined in this study were in close agreement with that reported by Ali et al (1985) and Abdalla et al (2007), but the amounts varied to a small extent from those reported by Muchiri et al (2012). Moreover, the concentrations of C 18:3 and C 20 in MSK fats were also good in line with that reported by Ali et al (1985) and Lakshminarayana et al (1983) for different mango varieties. However, the investigated fatty acid profiles of the promising MSK fats were also good in line with that reported by many researchers in the literature (Abdalla et al, 2007;Ali et al, 1985;Lakshminarayana et al, 1983;Solís-Fuentes & Durán-de-Bazúa, 2004).…”
Section: Fatty Acid Compositionssupporting
confidence: 90%
“…Moreover, the concentrations of C 18:3 and C 20 in MSK fats were also good in line with that reported by Ali et al (1985) and Lakshminarayana et al (1983) for different mango varieties. However, the investigated fatty acid profiles of the promising MSK fats were also good in line with that reported by many researchers in the literature (Abdalla et al, 2007;Ali et al, 1985;Lakshminarayana et al, 1983;Solís-Fuentes & Durán-de-Bazúa, 2004). The fatty acid compositions of the studied MSK fats were comparable in the contents of C 16 , C 18:0 , and C 18:1 with those of sal, shea, kokum, and illipe butter, but varied with respect to other component fatty acids.…”
Section: Fatty Acid Compositionssupporting
confidence: 89%
See 2 more Smart Citations
“…Solis-Frentes and Duran-de-Bazua (2004) reported notable similarities between the melt and crystallization profiles and solid fat content of MKF and CB. MKF has been reported to contain high content of stearic and oleic acids (Narasimha Char et al 1977;Van Pee et al 1980;Lakshminarayana et al 1983;Ali et al 1985;Solis-Frentes and Duran-de-Bazua 2004). The fat has also been reported to have a high SOS content with C 18:1 being most abundant acid in the middle sn-2 position (Holcapek et al 2005).…”
Section: Introductionmentioning
confidence: 99%